1999
DOI: 10.1073/pnas.96.18.10466
|View full text |Cite
|
Sign up to set email alerts
|

Serum choline activates mutant acetylcholine receptors that cause slow channel congenital myasthenic syndromes

Abstract: We have found that mutant acetylcholine receptor channels (AChRs) that cause slow-channel congenital myasthenic syndromes are activated by serum and that the high frequency of openings in serum is reduced by treatment with choline oxidase. Thus, slow-channel congenital myasthenic syndrome AChRs at the neuromuscular junction are likely to be activated both by steady exposure to serum choline and by transient exposure to synaptically released transmitter. Single-channel kinetic analyses indicate that the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 50 publications
2
73
0
Order By: Relevance
“…In effect, the CMS mutation turns the AChR from a two-site to a one-site receptor. The primary effect of many other CMS mutations is to decrease ⌬G 0 (31). The ⑀ProD2-L is an exception to this pattern because it has no effect on ⌬G 0 but a large one on ⌬G B ACh .…”
Section: Discussionmentioning
confidence: 99%
“…In effect, the CMS mutation turns the AChR from a two-site to a one-site receptor. The primary effect of many other CMS mutations is to decrease ⌬G 0 (31). The ⑀ProD2-L is an exception to this pattern because it has no effect on ⌬G 0 but a large one on ⌬G B ACh .…”
Section: Discussionmentioning
confidence: 99%
“…One laboratory (13) has used single channel analysis of ␣ 1 (K273E)␤ glycine receptors to measure an increase in the closing rate constant (Scheme 1, ␣), whereas other researchers have shown that ␣ 1 (R271Q) in the Gly-R reduces the single-channel conductance (25,40). Naturally occurring mutations of the TM2-TM3 loop in muscle nicotinic receptor subunits, which produce the slow-channel form of myasthenia gravis (41), alter the efficacy of the partial agonist choline by increasing the opening rate of the receptor (Scheme 1, ␤). The TM2-TM3 loop may therefore also play a role in the gating of other ligand-gated ion channels within this gene family.…”
Section: Discussionmentioning
confidence: 99%
“…Slow-Channel Syndrome Recent data suggest that slow-channel congenital myasthenic syndrome arises from a form of constitutive activation (Zhou et al 1999). Slow-channel congenital myasthenic syndrome is caused by dominant mutations in human muscle nicotinic acetylcholine receptors, resulting in muscle weakness and fatigue, especially revealed by staircase summation of the prolonged endplate potentials leading to a depolarization block at moderate rates (20-40 Hz) of stimulation.…”
Section: Gating Changes: Constitutive Activationmentioning
confidence: 99%
“…Single-channel analysis from the Sine and Auerbach labs previously disclosed the microscopic bases for these shifted dose-response relations: In general, the pore mutations increase ACh-activated currents by increasing the openchannel duration, whereas mutations at or near the agonist binding site increase the rate of opening , Sine et al 1995, Engel et al 1996, Milone et al 1997. Zhou et al (1999) have shown, additionally, that several slow-channel mutations produce receptors activated by choline. The 50% effective concentration for choline is between 500 lM and 3 mM, which causes detectable activation at choline concentrations normally found in extracellular fluid; indeed, serum does activate the mutant receptors.…”
Section: Gating Changes: Constitutive Activationmentioning
confidence: 99%